Rotational dependence of the branching ratios and fragment angular distributions for the photodissociation of 12C16O in the Rydberg 4p(2) and 5p(0) complex region (92.84–93.37 nm). Issue 26 (11th February 2019) - Jiang, Pan; Chi, Xiaoping; Qi, Wenke; Zhu, Qihe; Cheng, Min; Gao, Hong
Abstract : Various patterns of rotational dependence for the photodissociation branching ratios and irregular angular distributions of the photofragments have been observed. Abstract : 12 C 16 O shows complicated absorption structures in the wavelength range of 92.84–93.37 nm caused by the mutual interactions among the Rydberg 4p(2) and 5p(0) complexes, and several diffuse valence states. Here, we systematically measured the branching ratios and fragment angular distributions for the photodissociation of 12 C 16 O in the wavelength range using our mini-time-slice velocity-map imaging (mini-TSVMI) setup and a tunable vacuum ultraviolet (VUV) laser radiation source generated by the two-photon resonance-enhanced four-wave mixing scheme. Various patterns of rotational dependence for the photodissociation branching ratios have been observed for different vibronic states, and they are found to be consistent with previous spectroscopic investigations, revealing the complicated coupling schemes and predissociation dynamics in this region. Irregular angular distributions of the photofragments have been observed, especially in the Rydberg 5p(0) complex region. This has been attributed to the simultaneous excitation of multiple states with different symmetries in this region. The newly observed underlying continuum in the Rydberg 5p(0) complex region has been directly detected in the present study, and it is found to be of 1 Σ + symmetry and dissociates predominantly into the C( 3 P) + O( 3 P) channel. This study generally confirms the results of previous spectroscopic studies from a different perspective, and adds new knowledge for understanding the complicated predissociation dynamics of 12 C 16 O in the titled wavelength range.